(-6x-3)+(3x-2)=-11

Simple and best practice solution for (-6x-3)+(3x-2)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6x-3)+(3x-2)=-11 equation:


Simplifying
(-6x + -3) + (3x + -2) = -11

Reorder the terms:
(-3 + -6x) + (3x + -2) = -11

Remove parenthesis around (-3 + -6x)
-3 + -6x + (3x + -2) = -11

Reorder the terms:
-3 + -6x + (-2 + 3x) = -11

Remove parenthesis around (-2 + 3x)
-3 + -6x + -2 + 3x = -11

Reorder the terms:
-3 + -2 + -6x + 3x = -11

Combine like terms: -3 + -2 = -5
-5 + -6x + 3x = -11

Combine like terms: -6x + 3x = -3x
-5 + -3x = -11

Solving
-5 + -3x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -3x = -11 + 5

Combine like terms: -5 + 5 = 0
0 + -3x = -11 + 5
-3x = -11 + 5

Combine like terms: -11 + 5 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| (b+11)(b-11)= | | 4y+6=54 | | 5x^2+4xy-y^2=0 | | x^2-30x+1=0 | | 2x-3y=44 | | 3x^2+2x=4-7x | | x^2+4mx+8-4m=0 | | (12x^2)= | | 4m^2=24 | | y^(1/4) | | x^2-300x-30000=0 | | -1/3(3w-15)=-1/5(25-5w) | | 20p/3=40*3 | | (2y+1)(y-3)-3y(y+2)=y(2-y)+10 | | 2n-1=5n | | 8x12/4-?=2 | | 5m+12y=7y | | 4(2x+1)=6(x+12) | | 9(2x+3)=3(5x+4) | | 5(x+1)=4x+17 | | 3(x+9)=x+13 | | 4(x+4)=3x+22 | | x^2-90x-450=0 | | 5m+12=8md | | 2x+1=x^2-2x+1 | | 2682/8 | | ax^4+bc+c=0 | | 5-n/3=1 | | 8*3m=-3+6m | | x*0.07=1760 | | -2x-(x-1)+8=0 | | 4m+3m=1880 |

Equations solver categories